Tri‐Layered Nanocomposite Hydrogel Scaffold for the Concurrent Regeneration of Cementum, Periodontal Ligament, and Alveolar Bone. Issue 7 (27th January 2017) - Sowmya, S.; Mony, Ullas; Jayachandran, P.; Reshma, S.; Kumar, R. Arun; Arzate, H.; Nair, Shantikumar V.; Jayakumar, R.
Abstract : A tri‐layered scaffolding approach is adopted for the complete and concurrent regeneration of hard tissues—cementum and alveolar bone—and soft tissue—the periodontal ligament (PDL)—at a periodontal defect site. The porous tri‐layered nanocomposite hydrogel scaffold is composed of chitin‐poly(lactic‐ co ‐glycolic acid) (PLGA)/nanobioactive glass ceramic (nBGC)/cementum protein 1 as the cementum layer, chitin–PLGA/fibroblast growth factor 2 as the PDL layer, and chitin–PLGA/nBGC/platelet‐rich plasma derived growth factors as the alveolar bone layer. The tri‐layered nanocomposite hydrogel scaffold is cytocompatible and favored cementogenic, fibrogenic, and osteogenic differentiation of human dental follicle stem cells. In vivo, tri‐layered nanocomposite hydrogel scaffold with/without growth factors is implanted into rabbit maxillary periodontal defects and compared with the controls at 1 and 3 months postoperatively. The tri‐layered nanocomposite hydrogel scaffold with growth factors demonstrates complete defect closure and healing with new cancellous‐like tissue formation on microcomputed tomography analysis. Histological and immunohistochemical analyses further confirm the formation of new cementum, fibrous PDL, and alveolar bone with well‐defined bony trabeculae in comparison to the other three groups. In conclusion, the tri‐layered nanocomposite hydrogel scaffold with growth factors can serve as an alternative regenerative approach to achieve simultaneous and complete periodontal regeneration. Abstract : Tri‐layered nanocomposite hydrogel scaffold is developed to serve as an alternative regenerative approach to achieve simultaneous and complete regeneration of the lost periodontal tissues namely cementum, periodontal ligament, and alveolar bone. This layered approach with specific growth/induction factors can be applied to overcome the limitations of the current clinical periodontal therapy.